1998
DOI: 10.1590/s0034-89101998000600002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HIV positive status on sexual behavior among males

Abstract: ObjectiveTo compare HIV seronegative (HIV-) and HIV seropositive (HIV+) males in terms of sexual behavior with female and male partners of different types. MethodCross-sectional study. From August 1994 to February 1995, a sample of 236 respondents (150 HIV-and 86 HIV+) recruited from public health centers in the State of S. Paulo (Brazil), answered a questionnaire, including questions on demographic aspects, HIV and AIDS related knowledge, sexual orientation, use of alcohol and other drugs, sexual behavior wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…2,3 However, some studies among men have shown that they still engage in risky sexual behaviours even after learning that they are HIV-positive (HIV þ ). [4][5][6][7] Since the majority of women with AIDS were infected through sexual transmission, 1 research on the behaviour of men who have sex with women is extremely important to better understand heterosexual transmission of HIV. Prevention efforts for heterosexuals will only be effective if both men and women change their behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, some studies among men have shown that they still engage in risky sexual behaviours even after learning that they are HIV-positive (HIV þ ). [4][5][6][7] Since the majority of women with AIDS were infected through sexual transmission, 1 research on the behaviour of men who have sex with women is extremely important to better understand heterosexual transmission of HIV. Prevention efforts for heterosexuals will only be effective if both men and women change their behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…A aids como morte anunciada também aparece nas representações apresentadas pelos autores estudados (Alves, 2003;Santos et al, 2002;Guerriero, Ayres, Hearst, 2002;Barros et al, 2001;Silva et al, 2002;Ventura-Filipe, Newman, 1998). Essa associação, em parte, reforça-se pelo fato de, no final dos anos oitenta e meados dos noventa do século XX, essa doença ter sido responsável por significativas perdas de vidas, aparecendo como a principal causa de mortalidade para a população entre 15 e 49 anos, em alguns países, incluindo o Brasil (Santos et al, 2002;Silva et al, 2002).…”
Section: Representações Da Aidsunclassified
“…Associado à estabilidade dos relacionamentos e à confiança, outro aspecto que fortalece a ideia de não uso do preservativo é a intimidade entre parceiros. Nesse sentido, o uso do preservativo pode ser considerado dispensável em casa -com a esposa -e em outros tipos de relacionamentos envolvendo compromisso efetivo (Alves, 2003;Guerriero, Ayres, Hearst, 2002;Villarinho et al, 2002;Antunes et al, 2002), sendo aceito quando os/as parceiros/as são desconhecidos/as ou não são fixos/as (Alves, 2003;Gilbert, Madureira, 2008;Gondim, Kerr-Pontes, 2000;Gondim et al, 2009;Guerriero, Ayres, Hearst, 2002;Silva et al, 2002;Ventura-Filipe, Newman, 1998;Vilela, Doreto, 2006). Silva et al (2002) verificaram que o uso do preservativo foi consistente com parceiras casuais (73%) e foi inconsistente com parceiras fixas (27%).…”
Section: O Preservativo Como O Personagem Central Da Prevençãounclassified